Analisa Laporan Realisasi Anggaran RSUD Prov. NTB dalam Meningkatkan Nilai Ekonomi, Efektivitas dan Efisiensi Keuangan BLUD Tahun 2020-2022 - Nabila Izzaturrahmah Marasabessy; Sonny Fransisco Siboro; Nisa Hanifah; Raihan Syahrain (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research uses quantitative descriptive analysis to collect data, compare it with regulations, examine the advantages and disadvantages of the budget preparation process and realization reports, and draw conclusions. Results of calculations of economic ratios, efficiency and effectiveness of BLUD RSUD Prov. NTB for 2020-2022 is presented in tabular form. This discussion includes a comparison of economic ratios, efficiency and effectiveness for the relevant budget year. Analysis of the provincial hospital budget realization report. NTB is carried out to increase the economic value, effectiveness and financial efficiency of BLUDs with a focus on good governance and value for money. The analytical method used is descriptive analysis using secondary data from the Renja document and the Provincial Regional Hospital BLUD Budget Realization Report. NTB. This research aims to understand the process of preparing budgets and realization reports for the Provincial Regional Hospital. NTB to achieve community welfare through effective and efficient public sector budget management. By paying attention to economic ratios, efficiency and effectiveness in budget implementation, RSUD Provincial. NTB can identify areas that need to be improved to achieve better financial performance and provide optimal health services to the community.